The soluble CD83 protein prevents bone destruction by inhibiting the formation of osteoclasts and inducing resolution of inflammation in arthritis - Royzman, Dmytro; Andreev, Darja; Stich, Lena; Peckert-Maier, Katrin; Wild, Andreas B.; Zinser, Elisabeth; Mühl-Zürbes, Petra; Jones, Evan; Adam, Susanne; Frey, Silke; Fuchs, Maximilian; Kunz, Meik; et al. (Frontiers in Immunology, 2022)
Here we show that soluble CD83 induces resolution of inflammation in the antigen-induced arthritis (AIA) model. Joint swelling as well as arthritis related expression levels of IL-1β, IL-6, RANKL, MMP9 and OC-Stamp were strongly reduced, while Foxp3 was induced. In addition, we observed a significant inhibition of TRAP+ osteoclast formation, correlating with the reduced arthritic disease score. In contrast, cell specific deletion of CD83 in human and murine precursor cells resulted in an enhanced formation of mature osteoclasts. RNA-sequencing analyses, comparing sCD83- with mock treated cells, revealed a strong downregulation of osteoclastogenic factors, such as OC-STAMP, MMP9, NFATC1, Ctsk and Trap. Concomitantly, transcripts typical for pro-resolving macrophages, e.g. Mrc1/2, Marco, Klf4 and Mertk, were upregulated. Interestingly, also members of the metallothionein (MT) family, which have been associated with a reduced arthritic disease severity, were highly induced by sCD83 also in samples derived from RA patients. Finally, we elucidated the sCD83-induced signalling cascade, downstream to its binding to the Toll-like receptor 4/(TLR4/MD2) receptor complex, using CRISPR/Cas9-induced knockdowns of TLR4/MyD88/TRIF and MTs, revealing that sCD83 acts via the TRIF-signalling cascade. In conclusion, sCD83 represents a promising therapeutic approach to induce resolution of inflammation and to prevent bone erosion in autoimmune arthritis.